Early Jewish writings and New Testament interpretation - Elledge, Casey D. 1971- (New York, NY Oxford University Press, 2023)
'Early Jewish Writings and New Testament Interpretation' is a concise, introductory volume to orient undergraduates, seminarians and interested readers to some of the most important early Jewish writings that currently inform New Testament interpretation.
Also issued in print: 2023. - Includes bibliographical references and index. - Description based on online resource; title from PDF title page (viewed on May 18, 2023)
Keywords: Bible -- Criticism, interpretation, etc., Jewish; Bible -- Relation to the Old Testament; Jewish religious literature -- History and criticism; Judaism -- History -- To 70 A.D; Church History -- Primitive and early church, ca. 30-600; Religion; Religion & beliefs